Determination of antimicrobial activity of traditional spices extracts against clinical isolates in Dhaka city (Stamford Journal of Microbiology, 2021)
Spices are dried aromatic substances derived from plants and have demonstrated antimicrobial activity against pathogenic microorganisms. In the present study, a total of six spices turmeric (Curcuma longa), garlic (Allium sativum), black pepper (Piper nigrum), ginger (Zingiber officinale), clove (Syzygium aromaticum) and cinnamon (Cinnamomum verum) were evaluated for their antibacterial activity. Antibacterial activities of ethanol, propanol and water extracts were determined by agar well diffusion assay against previously isolated Klebsiella pneumoniae, Staphylococcus aureus from urine samples and Citrobacter spp. from throat swab samples. All spices examined in this study showed antibacterial activity in different types of extraction methods. Water, ethanol and propanol extracts exhibited anti-bacterial activity measured as zone of inhibition between 6 mm and 25 mm in diameter. Water extract of garlic (Allium sativum) showed the highest antibacterial activity (25mm) against clinical isolates of Staphylococcus aureus and Citrobacter spp. Water extract of other species showed the lowest antibacterial activity (6 mm) against throat swab isolates Staphylococcus aureus and Citrobacter spp. Spices which showed signifiant antimicrobial activities can be further studied for the isolation of active ingredients and development of novel drugs.Stamford Journal of Microbiology, Vol.11 (1) 2021: 17-19